Bringing to light a pedagogical heritage: An ergo-didactic approach - Güsewell, Angelika; Vivien, Rym; Terrien, Pascal (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2021)
This study aimed to provide first responses to the question whether the pedagogical heritage of an instrumental or vocal music teacher can be reconstructed by analysing and comparing the discourse and the teaching concerns of his or her former students. To address this question, a newly developed ergo-didactical approach (Author, 2018a) was used. The quantitative and qualitative analysis of simple and cross self-confrontation interviews conducted with six former students of the great violinist and violin instructor Veda Reynolds yielded strong similarities in the importance these former students seemed to attach to the five teaching concerns of the Bucheton and Soulé (2009) model in their own practice and in their discourse on Veda Reynold’s teaching.